Implementation of Digital Signature Using a SWOT Analysis to Improve Information Security - Nanda Irya; Denny Setiawan (InComTech : Jurnal Telekomunikasi dan Komputer, 2019)
At present in the digitalization era, online transactions continue to grow as well as digital signatures are becoming known to the public. Renewal of research and improvements continues to be made to improve the implementation of digital signatures in Indonesia. There needs to be research to find out the differences between the providers of electronic certificates that are developing in Indonesia. Digital signatures are expected to be able to simplify the administrative process and be implemented properly at Perum LKBN Antara. The application of digital signatures is protected by Ministerial Regulation No. 11 of 2018 and Government Regulation No. 82 of 2012 concerning the implementation of systems and electronic transactions (PSTE). In this study using the SWOT analysis (Standard, Weakness, Opportunities, Threat) as a problem solving method. There are 4 criteria assessed, namely the ease, security, work system and speed of the system category. In-depth discussion using the privyID application system. The application of using privyID is classified as good at Perum LKBN Antara.